2010
DOI: 10.17660/actahortic.2010.849.7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Ecogeographic Sampling and Phenotypic Diversity of Brazilian Psidium Germplasm Based on Categorical Descriptors

Abstract: Relationships between eco-geographic origin and phenotypic variation were established for 143 Psidium accessions, including "araçá" (a general term for wildgrowing Psidium spp. in Brazil) and guava (P. guajava) species, sampled in 31 different eco-geographic regions of ten Brazilian States. The accessions were characterized for 35 categorical traits according to the International Union for the Protection of New Varieties of Plants (UPOV) descriptors for P. guajava. The correlation between the cophenetic values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Previous molecular studies of Mexican guava germplasm have reported the lack of association between genetic grouping and geographical origin, mostly when including only local germplasm (Hernández‐Delgado et al, 2007; Sánchez‐Teyer et al, 2010). Likewise, associations between geographic origin and phenotypic diversity in Brazilian germplasm have not been observed (Fernandes‐Santos et al, 2010). Only a few studies have included accessions from different countries, in which case, there are clearer relationships between genetic diversity and geographic origin (Mehmood et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous molecular studies of Mexican guava germplasm have reported the lack of association between genetic grouping and geographical origin, mostly when including only local germplasm (Hernández‐Delgado et al, 2007; Sánchez‐Teyer et al, 2010). Likewise, associations between geographic origin and phenotypic diversity in Brazilian germplasm have not been observed (Fernandes‐Santos et al, 2010). Only a few studies have included accessions from different countries, in which case, there are clearer relationships between genetic diversity and geographic origin (Mehmood et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of molecular resources has limited genetic diversity studies in guava. Only a handful of diversity surveys have been conducted using low‐density marker panels, and these studies have generally been unable to reconstruct perceived associations between genetic, phenotypic diversity, and ecogeographic origin in Mexican (Sánchez‐Teyer et al, 2010), Brazilian (Fernandes‐Santos et al, 2010), and Pakistani guava germplasm (Mehmood et al, 2014). Few comprehensive studies have explored the global genetic diversity and differentiation of guava germplasm, although it undoubtedly exists (Mehmood et al, 2014).…”
Section: Introductionmentioning
confidence: 99%